Towards holistic colony feeding: Effects of vitamin supplementation on summer and winter honey bee workers, Apis mellifera L - Andrew F. Brown; Leah Guillaume-Gentil; Johanna Hehl; Stefan Niederer; Gina Retschnig; Peter Neumann (PLoS ONE, 2025)
In managed western honey bee, Apis mellifera, colonies, vitamins are often neglected when it comes to SI feeding despite their importance for health. Moreover, the potential links of vitamin feeding to longevity, food consumption and adult dry weight are poorly understood. Finally, comparative nutritional studies of short-lived summer workers and long-lived winter workers are currently lacking. Here, in a fully-crossed design, multivitamin supplementation of vitamins A, D, E, K, C, B1, B2, B3, B5, B6, B8, B9 and B12 (N = 13), titrated in three different dosages were fed to summer and winter workers in two trials. In standard laboratory hoarding cages, experimental workers were assigned one of eight treatments: Sucrose, Sucrose + Pollen, Vitamin 1, Vitamin 1 + Pollen, Vitamin 2, Vitamin 2 + Pollen, Vitamin 3, Vitamin 3 + Pollen (N = 8 treatments, 26 workers/cage, N = 64 cages/phase, N = 3328 total workers). Regardless of season, significant consumption polynomial trends were revealed; however, no significant differences in sucrose and pollen consumption were found. Likewise, none of the used multivitamin dosages did significantly improve any of the measured parameters. On the other hand, ad libitum access to pollen consistently increased both weight and lifespan, reinforcing pollen as critical to honey bee health. Additionally, the data clearly show that summer and winter workers bees display very similar significant patterns of dry weight and longevity. In particular, summer bees lived longer than winter ones. In light of well-known differences between summer and winter workers in the field, in particular longevity, these results are unexpected. Therefore, improved laboratory settings for honey bee s seem to be required to obtain more biologically relevant data and ultimately improve managed A. mellifera health.